Hydrodynamics of Steam-Water Two-Phase Flows ThroughGrooved Walled Passages - Vladimir Vladimirovich, Sinitsin; Pavel Alexandrovich, Taranenko; Khairuddin, Sanaullah; David, Bassir; Andrew Ragai, Henry Rigit (EDP Sciences, 2025)
In this study, we investigated the flow hydrodynamics of mixture of steam and water through a pipe that has groovedwalls. The walls were roughened using collars that has circular and squared shapes throughout the inner walls of the flowchannel. Our findings indicate that the factors related to the friction of the walls have been associated with wall roughness ranged from0.6to 0.63. The velocity deficit near the wall was slightly greater above the smooth walls compared to the rough walls, reflectingtheimpact of the friction factor. However, the profiles used to quantify the Reynolds normal stresses showed a distinct contrast. Inthe grooved surface channel, pressure-induced drag dominated, leaving little room for viscous effects and resulting in lower peaks. These stresses were heavily influenced by wall geometry. Notably, in channels with squared grooves, flowprofiles wereshows a slight decrease compared to those observed over smooth and rough walls.